2020
DOI: 10.3389/fneur.2020.00980
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Functional Connectivity in Stroke Patients With Basal Ganglia Damage and Cognitive Impairment

Abstract: Background: Stroke with basal ganglia damage (SBG) is a neurological disorder characterized by cognitive impairment. The neurobiological mechanism of cognitive impairment in stroke patients with basal ganglia damage (SBG patients) remains unclear. This study aimed to explore the underlying neurobiological mechanism of cognitive impairment in SBG patients using resting-state functional magnetic resonance imaging (rs-fMRI). Methods: The differences in functional connectivity (FC) between 14 SBG patients (average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
(44 reference statements)
5
21
1
Order By: Relevance
“…Here we provide evidence that the MoCA can be used to assess cognitive impairment of patients after basal ganglia stroke, and our analysis suggests that such stroke can indeed reduce cognitive function, consistent with previous studies [ 13 – 15 ]. In addition, our analysis shows that such stroke can reduce function in multiple cognitive domains.…”
Section: Discussionsupporting
confidence: 90%
“…Here we provide evidence that the MoCA can be used to assess cognitive impairment of patients after basal ganglia stroke, and our analysis suggests that such stroke can indeed reduce cognitive function, consistent with previous studies [ 13 – 15 ]. In addition, our analysis shows that such stroke can reduce function in multiple cognitive domains.…”
Section: Discussionsupporting
confidence: 90%
“…Here we provide evidence that the MoCA can be used to assess cognitive impairment of patients after basal ganglia stroke, and our analysis suggests that such stroke can indeed reduce cognitive function, consistent with previous studies (13)(14)(15). In addition, our analysis shows that such stroke can reduce function in multiple cognitive domains.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study showed that decreased functional connectivity (FC) between hippocampal and SMG was associated with impaired working memory function in stroke patients [ 31 ]. Similar results were also found in the previous studies focusing on the patients with acute BGIS which observed the decreased degree centrality (DC) and voxel-mirrored homotopic connectivity (VMHC) values in SMG [ 32 ]. Furthermore, aphasia is a common symptom in stroke [ 33 ].…”
Section: Discussionsupporting
confidence: 90%